High-resolution multi-channel seismic reflection (MCS) profiles from the southeastern North Sea acquired during expedition MSM98/2 - Arne Lohrberg; Jens Schneider von Deimling; Henrik Grob; Kai-Frederik Lenz; Sebastian Krastel (PANGAEA, 2023)
This dataset consists of three high-resolution multi-channel seismic reflection (MCS) profiles from the southeastern North Sea between Amrum and Heligoland shown in the corresponding publication. These data were acquired during expedition AL496 with R/V Alkor in July 2017 and during expedition MSM98/2 with R/V Maria S. Merian in February 2021 to image buried glacial landforms (tunnel valleys and a glacitectonic complex). All data have been processed to produce full seismic reflection profiles in the time-domain with an emphasis on the suppression of multiple reflections (shallow water artefacts). The raw seismic data (including navigation) is included in this dataset.